2014
DOI: 10.5223/pghn.2014.17.3.170
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Anomalous Pancreaticobiliary Ductal Union and Pathologic Inflammation of Bile Duct in Choledochal Cyst

Abstract: PurposeCholedochal cyst is a cystic dilatation of common bile duct. Although the etiology is presently uncertain, anomalous pancreaticobiliary ductal union (APBDU) is thought to be a major etiology of choledochal cyst. In this study, we analyzed the clinical and anatomical characteristics and pathologies of patients diagnosed with choledochal cyst in a single institute for 25 years.MethodsA total of 113 patients, diagnosed with choledochal cyst and who received an operation in Severance Children's Hospital fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…The CDC occurs predominantly in females with a reported ratio of 3:1 to 4:1, although the reason for this gender predisposition is unclear. 1,14 In the present study, we observed a female: male ratio of about 3:1, which is consistent with findings in available literature.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The CDC occurs predominantly in females with a reported ratio of 3:1 to 4:1, although the reason for this gender predisposition is unclear. 1,14 In the present study, we observed a female: male ratio of about 3:1, which is consistent with findings in available literature.…”
Section: Discussionsupporting
confidence: 93%
“…[16][17][18][19][20][21][22][23] (Table 6), though larger series from other parts of World have shown a weaker link. [13][14][15] The incidence of APBDJ has been found to be low in major Indian series as well. 15,[24][25][26][27][28][29] In the present study, APBDJ was present 20% of patients, which is consistent with previous findings in Indian patients ( Table 7).…”
Section: Discussionmentioning
confidence: 99%
“…Those of these malformations with cystic dilatation constitute the choledochal cyst. Although not proven, the commonly accepted theory [4][5] of their pathogenesis relies on the presence of an anomalous pancreaticobilliary junction (APBJ), which is seen in up to 90% patients with choledochal cyst. Lipsett [8,11] and Cho et al mentioned complete excision of extrahepatic component of choledochal cyst combined with cholecystectomy, followed by Roux-en-Y biliary reconstruction as the treatment of choice for type I and IV choledochal cyst.…”
Section: Discussionmentioning
confidence: 99%
“…Todani Type I cysts are the most common type and account for approximately 75% of patients. The most accepted theory in pathogenesis of choledochal cyst is Babbitt's theory' [3] is associated with anomalous pancreaticobiliary duct junction (APBDJ) [3][4]. Patients may present at any age with pain abdomen, jaundice and a right upper quadrant mass, however, 60 % of cases are diagnosed before the age of ten years [2].…”
Section: Introductionmentioning
confidence: 99%
“…Choledochal cyst is a cystic dilatation of the extra hepatic and/or intrahepatic bile duct 1 with an incidence of 1:1000 in Asian population. [2][3][4] It has female preponderance and female: male ratio is 3:1.…”
Section: Introductionmentioning
confidence: 99%